Dysfunctional positioning of the shoulder girdle and its impact on the biomechanics of the upper limb - Puchalska-Sarna, Anna; Sarna , Michał; Touma, Victor; Lenart–Domka, Ewa; Trzeciak, Jadwiga; Domino, Grzegorz (Technium BioChemMed, 2025)
The shoulder girdle plays a crucial role in upper limb mobility and stability. Dysfunctional positioning of the shoulder, such as rounded shoulder posture (RSP) or forward head posture (FHP), alters the biomechanics of the shoulder complex and may lead to musculoskeletal disorders. The glenohumeral joint, characterized by a relatively small and shallow glenoid cavity, relies on surrounding muscles and ligaments for stability. Key muscles influencing shoulder kinematics include the deltoid, rotator cuff muscles (supraspinatus, infraspinatus, teres minor, subscapularis), trapezius, serratus anterior, pectoralis minor, and latissimus dorsi. Muscle imbalances, weakness, or excessive tension can disrupt scapulothoracic and glenohumeral mechanics, resulting in compensatory movement patterns, reduced range of motion, pain, and increased risk of injuries such as subacromial impingement or shoulder dislocations. Postural abnormalities, prolonged sedentary behavior, and repetitive activities, such as smartphone use or athletic movements, exacerbate these dysfunctions. Effective assessment of shoulder position and muscle function, combined with targeted rehabilitation, is essential for restoring proper biomechanics, preventing injury, and improving functional outcomes. Understanding the interplay between shoulder posture, muscle activity, and joint mechanics provides a foundation for clinical interventions aimed at optimizing upper limb performance.